1998
DOI: 10.1046/j.1525-1497.1998.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing delirium by telephone

Abstract: To determine whether delirium can be diagnosed by telephone, we interviewed 41 subjects aged 65 years or older 1 month after repair of hip fracture, first by telephone and then face-to-face. Interviews included the modified telephone Mini-Mental State Examination and the Delirium Symptom Interview. Delirium was diagnosed using the Confusion Assessment Method diagnostic algorithm, and the telephone results were compared with the face-to-face results (the "gold standard"). Of 41 subjects, 6 were delirious by fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 9 publications
2
18
1
1
Order By: Relevance
“…However, this result remains significant even when adjusting for the level of pain. Although differences in patient population may account for the difference in findings compared with that reported by previous studies, our present results suggest that a randomized trial is necessary to further CAM ϭ confusion assessment method; CNS ϭ central nervous system; PCA ϭ patient-controlled analgesia; VAS ϭ verbal version of visual analog scale (0 -10) [linear tool widely used to measure pain from none (0) to severe (10)]. delineate the precise role of a postoperative method for postoperative pain management and postoperative delirium.…”
Section: Discussioncontrasting
confidence: 70%
“…However, this result remains significant even when adjusting for the level of pain. Although differences in patient population may account for the difference in findings compared with that reported by previous studies, our present results suggest that a randomized trial is necessary to further CAM ϭ confusion assessment method; CNS ϭ central nervous system; PCA ϭ patient-controlled analgesia; VAS ϭ verbal version of visual analog scale (0 -10) [linear tool widely used to measure pain from none (0) to severe (10)]. delineate the precise role of a postoperative method for postoperative pain management and postoperative delirium.…”
Section: Discussioncontrasting
confidence: 70%
“…Six months after discharge from the RCU, our research nurse telephoned survivors to administer the validated telephone version of the Confusion Assessment Method (CAM) after a preliminary assessment of the patient's level of consciousness and capacity to respond (16). If a family member or caregiver reported that the patient was too impaired to respond, the nurse used a formal, written protocol to clarify whether the impairment was cognitive and/or physical by asking systematically and in detail whether the patient was (1) too physically weak or otherwise physically impaired to move to, hold, or speak into a phone; or whether (2) the patient was unable to respond to the telephone interview because of an alteration of consciousness (other than normal sleep or ORIGINAL RESEARCH drowsiness), confusion, dementia, or other cognitive impairment.…”
Section: Main Outcome Variablementioning
confidence: 99%
“…Because of the accuracy, brevity, and ease of use by clinical interviewers, the Confusion Assessment Method (CAM) has become the most widely used standardized delirium instrument for clinical and research purposes over the past 16 years [5]. It has been adopted for use in a variety of settings such as the intensive care unit [2], emergency rooms [8], and at home via telephone surveys [10]. The CAM was developed to allow nonpsychiatrically trained personnel (either clinical or research staff) to quickly and accurately identify patients with delirium.…”
mentioning
confidence: 99%